High School Students' Performance Indicators in Distance Learning in Chemistry during the COVID-19 Pandemic - Manal AlMahdawi; Salieu Senghore; Horia Ambrin; Shashidhar Belbase (MDPI AG, 2021)
All private and public schools in the UAE had to run online classes as they closed their face-to-face classes due to the COVID-19 pandemic in the spring of 2021. In this context, the purpose of this study was to investigate the indicators of high school students' performance in online chemistry classes in a private school in Al Ain, UAE. A quantitative study with an online survey questionnaire was carried out with 101 participants. The data were analyzed using One-Sample Wilcoxon Signed Ranked Test, Independent Sample Mann Whitney U, Independent Sample Kruskal Wallis H, and Spearman's Rank Correlation in the Statistical Package for Social Sciences (IBM SPSS 26). The findings revealed that there was a statistically significant positive impact on critical thinking, collaborative skills, creativity and innovation, technology application, class participation, and overall achievement during online and distance learning of chemistry. There was a statistically significant difference in students' critical thinking, collaborative skills, creativity and innovation, class participation, and achievement by gender and nationality. These skills were not statistically significantly different across students of grades 10, 11, and 12, except for creativity and innovation, which were significantly different between students of grades 11 and 12. All the six indicators of students' performance had a significant correlation between each other, with the highest correlation between collaborative skills and participation level. These findings indicated that students' performance in online chemistry classes during the COVID-19 pandemic provided opportunities to develop creativity and collaborative skills, together with better learning achievement as perceived by the students.